Cortical Areas Related to Attention to 3D Surface Structures Based on Shading: An fMRI Study - Taira, Masato; Nose, Izuru; Inoue, Kentaro; Tsutsui, Ken-ichiro (NeuroImage (Orlando, Fla.), 2001)
Theaim of the present study was to determine which cortical areas are activated in relation to attention to a three-dimensional (3D) structure of a surface based on shading. Cortical activities were examined using functional magnetic resonance imaging while subjects discriminated whether the central part of the surface protruded or was recessed based on shading without any binocular disparity cues. Relatively broad cortical areas including both dorsal and ventral visual pathways were recruited when shading was used as a crucial cue for the perception of the 3D structure of a surface. In these cortical areas, however, the right intraparietal area was shown to be commonly activated in all subjects and in all sessions by multisubject conjunction analysis. These results strongly suggest that the intraparietal area plays an important role in perception of the 3D structure of a surface, even when based only on monocular depth cues without binocular disparity cues.